Analysis of Supply Chain Management Affecting the Underpricing of Companies Conducting Initial Public Offerings (IPO) on Indonesia Stock Exchange in 2018 - Priyanto, Rame; Herawati, Aty (ExcelingTech, 2020)
Abstract- In the initial public offering activities of the company to obtain funds from the public, there is often an underpricing phenomenon, which is when the determination of the company's stock price at the time of an IPO is lower than the price that occurs on the secondary market on the first day. This study aims to analyze the influence of supply chain management (underwriter reputation, supply chain management reputation, firm age, and percentage of the public offering to underpricing of companies conducting IPO on the Indonesia Stock Exchange in 2018). Research data were cross-section data with observation period from 2nd January to 31st December 2018. The sampling method used was purposive sampling. From the population of 57 companies conducting IPOs, 54 issuers met the sample criteria. The analytical method used in this study was multiple linear regression. The results showed that the reputation of the underwriter, supply chain management's reputation, firm age, and percentage of public offering simultaneously influenced underpricing. Partially, the reputation of the underwriter and supply chain management's reputation have a significant negative effect, while the firm age and the percentage of the public offering do not have a significant effect. Underwriter reputation has the biggest influence on underpricing.